2014
DOI: 10.5194/hessd-11-1821-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrological, ecological, land use, economic, and sociocultural evidence for resilience of traditional irrigation communities in New Mexico, USA

Abstract: Abstract. Southwestern US irrigated landscapes are facing upheaval due to climate change-induced water scarcity and economic change-induced land use conversion. Clues to community longevity are found in the traditionally irrigated valleys of northern New Mexico. Human systems have interacted with hydrologic processes over the last 400 yr in river fed irrigated valleys to create linked systems. In this study, we asked if concurrent data from multiple disciplines show that human adapted hydrologic and socioecono… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Simultaneously, the groundwater table in this region was the lowest (WTD around 4.6 ± 2.7 m), which even reached a depth of 6.3 m in 2011. As groundwater can be recharged by ephemeral runoff seepage, irrigation return flow, and subsurface lateral inflow , irrigation plays a pivotal role in the extended phreatic water recharge to groundwater (Meredith and Blais, 2019), assuming a critical function in sustaining agricultural production and fostering community stability in arid regions (Fernald et al, 2015). However, groundwater depth, salinity, and major ion concentrations could notably impact the composition and distribution of the plant community (Zeng et al, 2020).…”
Section: Groundwater Tds Responses To Irrigation In Lower Regionmentioning
confidence: 99%
“…Simultaneously, the groundwater table in this region was the lowest (WTD around 4.6 ± 2.7 m), which even reached a depth of 6.3 m in 2011. As groundwater can be recharged by ephemeral runoff seepage, irrigation return flow, and subsurface lateral inflow , irrigation plays a pivotal role in the extended phreatic water recharge to groundwater (Meredith and Blais, 2019), assuming a critical function in sustaining agricultural production and fostering community stability in arid regions (Fernald et al, 2015). However, groundwater depth, salinity, and major ion concentrations could notably impact the composition and distribution of the plant community (Zeng et al, 2020).…”
Section: Groundwater Tds Responses To Irrigation In Lower Regionmentioning
confidence: 99%
“…Few studies document the irrigation efficiency trap from farm-scale decisions to basin-scale hydrologic outcomes with measured social and physical data (e.g., Wheeler et al, 2020;Anderson, 2022). But irrigation systems are complex socialecological systems (Lam, 2004) and integrating the hydrologic and social components of irrigation efficiency are important for system understanding and resilience (Fernald et al, 2015;Dunham et al, 2018). To adapt and prepare accordingly, we must examine place-based farm-scale irrigation decisions and how these decisions collectively impact basin-scale hydrology.…”
Section: Introductionmentioning
confidence: 99%
“…The so-called "spate irrigation" is one of the oldest traditional irrigation systems widely used all over the world. It is found especially in the Middle East, North Africa, West Asia, East Africa, Europe, and parts of Latin America (Van Steenbergen et al 2011;Fernald et al, 2015;Leibundgut & Kohn, 2014). However, this irrigation system underwent a considerable decline in the second half of the 20 th century (Leibundgut & Kohn, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…However, this irrigation system underwent a considerable decline in the second half of the 20 th century (Leibundgut & Kohn, 2014b). This system has been in practical use in very different and contrasted environmental regions around the globe (Fernald et al, 2015;Leibundgut & Kohn, 2014;Mehari et al, 2007;Tesfai, & Stroosnijder, 2001). For instance, in the semi-arid upper Rio Grande of the United States, Fernald et al (2015) reported that community irrigation systems, known as Acequia, which is derived from the word seguia in Arabic meaning an irrigation channel, have been governed by users to divert water from streams to irrigate northern New Mexico's agriculture for centuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation